GABAergic System Dysfunction in Autism Spectrum Disorders - Zhao, Haisheng; Mao, Xijing; Zhu, Cuilin; Zou, Xiaohan; Peng, Fanzhen; Yang, Wei; Li, Bingjin; Li, Guangquan; Ge, Tongtong; Cui, Ranji (Frontiers in Cell and Developmental Biology, 2022)
Autism spectrum disorder(ASD) are a series of neurodevelopmental diseases characterized by two core symptoms, social impairments and repetitive behaviors. GABAergic inhibitory neurotransmission is critical in regulation of brain rhythm and spontaneous neuronal activities during neurodevelopment. Human genetic studies identified some genetic variations associated with GABA system, indicating abnormal GABAergic neurotransmission might underlie the pathogenesis of ASD. However, the molecular mechanisms in which the GABAergic synaptic transmission involved in ASD remain unclear. Transgenic technology enable translating genetic variations into rodents models to further investigate the structural and functional synaptic dysregulation in ASD. In this review, we summarized evidence from human neuroimaging and postmortem studies, genetic and pharmacological models and put emphasize on the GABAergic synaptic dysregulation and consequent E/I imbalance. We attempt to illuminate pathophysiological role of structural and functional synaptic dysregulations in autism and provide insights for future investigation.